ANALISIS PENGARUH MOTIVASI KERJA DAN KERJASAMA TIM TERHADAP KINERJA DIVISI PEMASARAN PT. SARANA BHUANA JAYA BANDUNG - Rasty Yulia; Heny Herawati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
This research was conducted to determine the effect of work motivation and teamwork on the performance of the marketing division of PT. Facilities Bhuana Jaya Bandung. In this study, questionnaires were distributed to 20 respondents. This research was conducted at PT. Sarana Bhuana Jaya Jl. Northern Mars III No. 36 Bandung. The research method used is the census method and the analytical tool used is quantitative analysis (multiple regression) using the SPSS version 26.0 program. The results of this study indicate that the magnitude of the simultaneous influence between work motivation and teamwork on the performance of the marketing division of PT. Sarana Bhuana Jaya Bandung This research is expected to provide benefits to the management of PT. Sarana Bhuana Jaya Bandung to keep implementing teamwork, and trying to generate initiative in each team member in carrying out their duties by giving them the freedom to take initiative, to be innovative and to be rewarded.